Network analysis of interpersonal conflict, emotional exhaustion and psychological distress among mental health nurses in the workplace: a cross-sectional survey - Qiu, Fangxinrui; Li, Yuan; Zhou, Chunfen; Sun, Yidan; Li, Jie; Tang, Jiao (Frontiers in Public Health, 2025)
BackgroundMental health nurses (MHNs) frequently engage in intense interpersonal interactions and encounter various forms of conflict with patients, colleagues, and their families. These conflicts can disrupt workplace harmony and significantly affect nurses' mental wellbeing. This study aims to analyze how workplace interpersonal conflicts affect nurses' emotional exhaustion and psychological distress through structural network analysis.MethodsA cross-sectional descriptive correlational survey was conducted using the Customer Interpersonal Injustice Scale, Interpersonal Conflict at Work Scale, Bi-directional Work-Family Conflict Scale, Maslach Burnout Inventory (emotional exhaustion sub-scale), and the 6-item Kessler Psychological Distress Scale. The survey was completed by 858 MHNs and 643 non-MHNs across six comprehensive hospitals and nine psychiatric hospitals from western China.Results5.1% of all participants reported severe distress. Emotional exhaustion and psychological distress were associated with lower subjective social status, more severe conflicts with patients and supervisors, and bidirectional work-family conflict. Key risk factors for severe psychological distress included being an MHN, patient mistreatment, and bidirectional work-family conflict, while higher subjective social status was a protective factor. Network analysis showed no significant differences in conflict structures between MHNs and non-MHNs. Within the network, the work-to-family conflict most significantly impacted emotional exhaustion, while emotional exhaustion had the greatest influence on psychological distress.ConclusionThis study revealed that MHNs experienced a higher rate of severe psychological distress than non-MHNs, with emotional exhaustion and psychological distress closely associated with subjective social status and interpersonal conflict. Given that work-to-family conflict and emotional exhaustion were key nodes in the network, targeted interventions are urgently needed to alleviate psychological distress.